(untitled) - Broukal, Milada (Boston, 1995)
The Heinle & Heinle TOEFL test Assistant: Vocabulary is a vocabulary building text that prepares students to meet the vocabulary needs in all sections of the TOEFL test; i.e., Listening Comprehension, Structure and Written Expression, and Vocabulary and Reading Comprehension, in a variety of ways. Each section of the test has different vocabulary needs. The Listening Comprehension section requires vocabulary in the form of idioms, phrasal verbs, everyday and specific vocabulary. The Structure and Written Expression section tests knowledge of suffixes, and of confusing words. The Vocabulary and Reading Comprehension section requires looking for contextual clues that reveal the meaning of a word. This comprehensive text addresses all the vocabulary needs of the student.
Keywords: Test of english as a foreign language,English language,Vocabulary; Study guide,Textbooks for foreign speakers,Examinations,Study guide